"Ex priore Saulo Paulus vocari amavit": renombrar y convertir : el caso del Apóstol en Agustín - Rosa, Fabio (Avgvstinvs, 2025)
In Acts 13:9, the Apostle is mentioned with the double name Saul/Paul. From that moment on, he is always referred to by his second name, and this is how he appears in his letters as well. We do not know why he wanted to change his name - whether he was called Paul at birth or adopted the new name after his conversion. Since Origen, the issue has been widely debated. Based on the etymology of the name, Augustine interpreted this change as a gesture of humility resulting from the Damascus event, and he created the account of the lupus mutatus in agnum (wolf changed into lamb), a narrative destined to become fixed in the collective imagination. These pages examine the role that this story played in the work of the Bishop of Hippo, either as a hermeneutical key to his theology of grace or as a reminder of his own conversion.